COBALT (II) AND NICKEL (II) COMPLEXES WITH SCHIFF BASE LIGANDS 1,2-DIPHENYL-2-ALKYLIMINOETHAN-I-ONE OXIME - RAI, H.C.; KUMAR, RAMESH; ALA, SIIASIIIK; SHARMA, N.N. (Biological Sciences - PJSIR, 1995)
A number of complexes ofthe type [M(I-1J.,1· )lXl]when: M=Ni(I1), Co(ll); I-1L’- =SchifThascligands derived by the condensation of I.2-diphenyl-l-hydroxyiminoethan-2-one with n-butylamine (I-ILl), isobutylamine (HLl), n- propylamine (I-1U)and isopropylamine (HL’): X= CI’, 1Jr",I’, NO’3and CIO’4 have been synthesized and characterised on the basis of elemental analysis. magnetic susceptibility, conductivity, infrared and electronic spectral data.